1997
DOI: 10.1002/(sici)1097-0215(19970807)72:4<556::aid-ijc2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases and their inhibitors in human bronchopulmonary carcinomas: Quantificative and morphological analyses

Abstract: The expression of various matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) in 88 primary bronchopulmonary cancers and in 13 neighbouring pulmonary parenchyma samples was quantified by Northern-blot analysis, and morphologically examined by in situ hybridization and immunohistochemistry in order to evaluate the involvement of MMPs in the pathophysiology of these carcinomas and to look for potential markers of aggressivity of lung tumours. Northern-blot analysis showed that the predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
68
1
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 15 publications
10
68
1
4
Order By: Relevance
“…The most important inference of our study is that both type IV collagenases tested are significantly overproduced in tumor tissue compared with uninvolved lung. Our results are only partially consistent with those obtained by others (Urbanski et al 1992;Nawrocki et al 1997;Kodate et al 1997;Brown et al 1993). Two studies on lung cancer using Northern analysis, immunohistochemistry, and in situ hybridization (Urbanski et al 1992;Nawrocki et al 1997) showed that MMP-9 was absent from normal lung parenchyma, whereas we detected this enzyme in all specimens tested, although the total MMP-9 activity was twofold higher in lung cancer preparations than in normal lung parenchyma, and the activation in half of the cases of lung cancer was visible.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The most important inference of our study is that both type IV collagenases tested are significantly overproduced in tumor tissue compared with uninvolved lung. Our results are only partially consistent with those obtained by others (Urbanski et al 1992;Nawrocki et al 1997;Kodate et al 1997;Brown et al 1993). Two studies on lung cancer using Northern analysis, immunohistochemistry, and in situ hybridization (Urbanski et al 1992;Nawrocki et al 1997) showed that MMP-9 was absent from normal lung parenchyma, whereas we detected this enzyme in all specimens tested, although the total MMP-9 activity was twofold higher in lung cancer preparations than in normal lung parenchyma, and the activation in half of the cases of lung cancer was visible.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are only partially consistent with those obtained by others (Urbanski et al 1992;Nawrocki et al 1997;Kodate et al 1997;Brown et al 1993). Two studies on lung cancer using Northern analysis, immunohistochemistry, and in situ hybridization (Urbanski et al 1992;Nawrocki et al 1997) showed that MMP-9 was absent from normal lung parenchyma, whereas we detected this enzyme in all specimens tested, although the total MMP-9 activity was twofold higher in lung cancer preparations than in normal lung parenchyma, and the activation in half of the cases of lung cancer was visible. Contrary to the results obtained by other researchers (Urbanski et al 1992;Nawrocki et al 1997), Brown et al, using gelatin zymography, detected MMP-9 activity in all normal non-neoplastic lungs and in all specimens of non-small cell lung cancer (NSCLC) (Brown et al 1993).…”
Section: Discussionsupporting
confidence: 89%
“…Investigations on potential new prognostic markers are, therefore, an important prerequisite for the development of optimized therapy strategies. MMP-2 and MMP-9 have been reported to be associated with tumor progression in various types of cancer, and several studies have reported their role in PCa [4,5,6,15,19,21,25,35]. This is the first report in which the expression and activity of MMP-2 and MMP-9 has been investigated in prostatic tumor tissue from core needle biopsies and radical prostatectomies, as well as serum probes of the same patient group.…”
Section: Discussionmentioning
confidence: 83%
“…They specifically cleave type-IV collagen, the major structural component of basement membranes. Increased expression of MMP-2 and MMP-9 has been associated with malignant progression in various cancer types, such as breast, lung or colorectal cancers [4,6,15,19,25,35]. Studies on MMP-2 and MMP-9 expression and activity in human PCa have been focused on cell culture systems or blood specimens of cancer patients [5,8,14,21,33], although only sparse data is available for prostatic tissue directly [2,9,26,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The over-expression of MMPs, leading to a disruption of the balance between MMPs and TIMPs, has been extensively reported in various carcinoma types. In that way, MMPs have been implicated in early as well as in late stages of cancer progression, in particular in cell growth, invasion, angiogenesis, and metastasis (Chambers and Matrisian 1997;Curran and Murray 1999;Egeblad and Werb 2002;Nawrocki et al 1997;Park et al 2004). MMP over-expression is also associated with the acquisition of invasiveness by tumor cells in vitro.…”
Section: Discussionmentioning
confidence: 99%